دراسة تأثير أنواع حاملات اللهب على استقرارية وتوزيع الحراري لجبهةاللهب الانتشاري - الملقي محمد جلال; عبد كرم الله عبدالحسن; عبدالكريم الجاف جاسم محمد (Latakia University Journal -Engineering Sciences Series, 2019)
في البحث الحالي درست إمكانات الحصول على أعلي توزيع لدرجة حرارة اللهب الانتشاري في شروط الاستقرارية العالية، ذلك برفع كفاءة الخلط بين الوقود والهواء، وزيادة إثارة تيارات الهواء المرتدة بواسطة تغيير الشكل الهندسي لحامل اللهب. أجريت الدراسة التجريبية والنظرية في شروط الجريان الصفائحي والجريان الاضطرابي، ولهذا الغرض تم تصميم وإعداد الحراق الانتشاري. في التجارب استخدمت ثلاثة أنواع لحاملات اللهب هي:حامل اللهب القرصي ذو البروزات الاسطوانيةDisc with Cylindrical Rods Bluff-Body [D.C.R.B.B.]، وحامل اللهب المخروطي المجوف Hollow Cone Bluff-Body [H.C.B.B.]،اما الثالث فهو حامل اللهب المخروطي المجوف مع البروزات الاسطوانية (المركب) (Combined Bluff-Body). تم قياس توزيع درجة حرارة جبهة اللهب الانتشاري، وحسابها تجريبياً ونظرياً، وتم الحصول على أعلى درجة حرارة لجبهة اللهب عند منطقة الخلط المثالي بين الوقود والهواء، وذلك عن طريق الاقتراب من الاحتراق الكفوء والتوازن الكيميائي والحراري المثالي، أظهرت النتائج بأن أفضل عملية خلط وانتشار بين وقود غاز البترول المسال (LPG) مع الهواء تحدث عند استخدام حامــل اللهب المركب، حيث تم رفع درجة حرارة جبهة اللهب الى (4.8%) عند منتصف فوهة الحراق و(28.57%) عند الحافة الخارجية للحراق مقارنة، مع البحوث السابقة المنشورة. In the present research, the possibilities to obtain the highest temperature distribution of diffusion flame at higher stability conditions through activating the proper mixing of fuel with air and increasing the excitation of the returned air flow by changing the geometrical shape of the bluff-body, were studied. The experimental and theoretical studies were carried out under the conditions of laminar flow and turbulent flow. For this purpose, a diffusion burner was designed and prepared. During the tests, three types of bluff bodies were used: disc with cylindrical rods bluff-body [D.C.R.B.B.], hollow conical bluff-body [H.C.B.B.], and hollow conical with cylindrical rods bluff-body (combined bluff-body). The temperature distribution of diffusion flame front was measured and calculated empirically and theoretically. As well, the highest temperature of the flame front at the ideal mixing between fuel and air were obtained, by approaching the efficient combustion of thermal and chemical ideal equilibrium. The results showed that the best process of mixing and the diffusion between the liquefied petroleum gas (LPG) with air occurs when you use the combined bluff-body. The temperature flame front was raised to the (4.8%) in the middle of center line burner and (28.57%) at the outer edge of the burner when compared with the published researches.